Data mining with decision trees : theory and applications - Rokach, Lior. (Colección de libros electrónicos de ULoyola, 2015)
Decision trees have become one of the most powerful and popular approaches in knowledge discovery and data mining; it is the science of exploring large and complex bodies of data in order to discover useful patterns. Decision tree learning continues to evolve over time. Existing methods are constantly being improved and new methods introduced.This 2nd Edition is dedicated entirely to the field of decision trees in data mining; to cover all aspects of this important technique, as well as improved or new methods and techniques developed after the publication of our first edition. In this new edition, all chapters have been revised and new topics brought in. New topics include Cost-Sensitive Active Learning, Learning with Uncertain and Imbalanced Data, Using Decision Trees beyond Classification Tasks, Privacy Preserving Decision Tree Learning, Lessons Learned from Comparative Studies, and Learning Decision Trees for Big Data. A walk-through guide to existing open-source data mining software is also included in this edition.This book invites readers to explore the many benefits in data mining that decision trees offer:Self-explanatory and easy to follow when compactedAble to handle a variety of input data: nominal, numeric and textualScales well to big dataAble to process datasets that may have errors or missing valuesHigh predictive performance for a relatively small computational effortAvailable in many open source data mining packages over a variety of platformsUseful for various tasks, such as classification, regression, clustering and feature selectionContents:Introduction to Decision TreesTraining Decision TreesA Generic Algorithm for Top-Down Induction of Decision TreesEvaluation of Classification TreesSplitting CriteriaPruning TreesPopular Decision Trees Induction AlgorithmsBeyond Classification TasksDecision ForestsA Walk-through Guide for Using Decision Trees SoftwareAdvanced Decision TreesCost-sensitive Active and Proactive Learning of Decision TreesFeature SelectionFuzzy Decision TreesHybridization of Decision Trees with Other TechniquesDecision Trees and Recommender SystemsReadership: Researchers, graduate and undergraduate students in information systems, engineering, computer science, statistics and management.